2022
DOI: 10.3390/ijms231911127
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Successfully Treated Double Valve Infective Endocarditis Caused by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a rare yet particularly aggressive infective endocarditis pathogen. We describe a case of successfully managed double-valve P. aeruginosa infective endocarditis, in which the presumed source of bacteremia was a long-term tunneled central venous catheter used for hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Bilateral IE may be related to congenital heart diseases or defects, intra-cardiac devices, or repeated injections by drug users [22,37,41]. There are few cases of right-and left-sided MVE in the literature [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In addition to our patient, we have found in the literature another 21 clinical cases, which are outlined in Table 1.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Bilateral IE may be related to congenital heart diseases or defects, intra-cardiac devices, or repeated injections by drug users [22,37,41]. There are few cases of right-and left-sided MVE in the literature [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. In addition to our patient, we have found in the literature another 21 clinical cases, which are outlined in Table 1.…”
Section: Discussionmentioning
confidence: 66%
“…We included all the papers that met the following criteria: We identified 1699 studies reporting data on MVE (Figure 2). Among them, 20 papers reported 21 clinical cases on bilateral MVE [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Table 1 describes demographic, clinical, and microbiological characteristics as well as the prognosis of the 21 clinical cases identified and of our case.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Given that the tricuspid valve (TV) is anteriorly located, 3D TOE should yield a more accurate assessment than 2D TOE. Two studies 28,37 and a few case reports 38,39 assessed the potential advantages of 3D TOE in patients with the TV or cardiac device-related IE. One investigation showed that in 90% of patients, 3D TOE enabled the comprehensive examining of all TV leaflets and the subvalvular apparatus, while 2D TOE failed to detect vegetation in 50% of the patients.…”
Section: Right-sided Ie and Intracardiac Devicesmentioning
confidence: 99%
“…Surgical interventions, such as the correction of congenital heart disease and the insertion of prosthetic valves or cardiac devices, including implantable cardioverters or pacemakers, have led to major changes in this condition. The involvement of native valves usually requires a damaged structure, and it commonly affects the mitral valve [ 4 , 5 , 6 ]. Rare presentations may include a concomitant infection of two valves [ 3 ], but studies and case reports have not described the simultaneous involvement of native and prosthetic valves.…”
Section: Introductionmentioning
confidence: 99%